Development of a STEAM-based Papercraft Media 'Memoo!' to Enhance Fine Motor Skills in Early Childhood - Jazila Anaka Putri; Evi Selva Nirwana; Alimni Alimni (AL-ISHLAH: Jurnal Pendidikan, 2025)
Fine motor development is a foundational aspect of early childhood learning, supporting skills such as writing, drawing, and object manipulation. Despite its importance, there is a lack of integrated learning media that stimulate fine motor skills through engaging, structured, and cognitively rich activities. This study introduces Memoo!, a STEAM-based papercraft medium designed to enhance fine motor skills in children aged 5–6. This research used a Research and Development (RD) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Memoo! was developed as a 3D cow-themed papercraft integrating STEAM elements—science exploration, engineering assembly, creative art, mathematical shape recognition, and early literacy. The media was validated by experts and tested on 14 children at TK IT Syuhada Bengkulu. Data collection involved expert validation checklists, teacher practicality questionnaires, and pretest-posttest observations of children’s fine motor skills. Validation results showed high feasibility, with experts rating the media as suitable for early childhood use. Teachers reported ease of use and strong child engagement. Children demonstrated a statistically significant improvement in fine motor performance, with an average score increase of +8.86 points (p 0.05) after using the media. Observed gains included better cutting, folding, pasting, and eye–hand coordination. The findings indicate that Memoo! is a valid, practical, and effective medium for developing fine motor skills through STEAM-based learning. Future studies are encouraged to expand the sample size and explore long-term effects in diverse educational contexts.